PENGEMBANGAN MEDIA PERMAINAN PENEMUAN HARTA KARUN FINDING TREASURE PADA SUB POKOK BAHASAN RESPIRASI SEL - ULFATUL MASRUROH (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Finding Treasure game media is one of the instructional innovation to strength the concept of student in the conceptual material such as cell respiration. The development of game media is expected to be able to make a joyful learning condition. This research was conducted to produce Finding Treasure game media in the cell respiration subtopic which is feasible that wil be reviewed from the aspect of validity media. The results showed that the validity of media obtained the result as big as 3,76 (very feasible). The conclusion of this research showed that Finding Treasure game media was feasible to applied in the learning activity. Keywords: The development, Finding Treasure game media, cell respiration.